1996
DOI: 10.1016/s0886-3350(96)80189-1
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive keratectomy for residual myopia after radial keratotomy

Abstract: Photorefractive keratectomy was efficacious in correcting residual myopia after RK in a group of selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Finally, 44 articles were selected for full-text evaluation, and after a thorough assessment, 35 studies were selected for final analysis, with their characteristics presented in Table 1. 12–46 The PRISMA flowchart for this review is shown in Supp. 1 (available at http://links.lww.com/JRS/B106).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 44 articles were selected for full-text evaluation, and after a thorough assessment, 35 studies were selected for final analysis, with their characteristics presented in Table 1. 12–46 The PRISMA flowchart for this review is shown in Supp. 1 (available at http://links.lww.com/JRS/B106).…”
Section: Resultsmentioning
confidence: 99%
“…If the opacity is only situated superficially, as in the initial stage of the disease and in recurrences, abrasion [14,15], superficial keratectomy without covering [12,16], phototherapeutic keratectomy [1,5,6,9] and lamellar keratoplasty [13] are recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Predictability has become a commonly used term in connection with refractive surgery,1 2 both in the assessment of results and for the counselling of patients who present themselves for possible treatment. What, however, does the term now mean?…”
mentioning
confidence: 99%